Sikap Siswa SMP Perintis 1 Terhadap Nilai Nasionalisme Dari Pelestarian Seni Budaya Lokal - Monica Pricillia A Y; Adelina Hasyim; Yunisca Nurmalisa (FKIP Unila, 2017)
The objective of this research is to explain about students' attitude in Junior High School Perintis 1 Bandar Lampung toward nationalism value of preserving local art and culture. This research used descriptive method. Population of this research is students of Junior High School Perintis 1 Bandar Lampung that has 184 students, and sample of this research is 18 students. Meanwhile, data gathering technique of this research used questionnaire, interview, observation, and documentation. Lastly, data analysis technique of this research used interval formula and percentage. The result of the research showed that students' comprehension indicator from 7 respondents or 38,9% gave agree responses that showed students have understood about preserving local art and culture is the responsible of young generation. Appreciation indicator from 8 respondents or 44,4% gave agree responses toward nationalism value from preserving local art and culture because the students have a role in keeping an eye of national stability with preserving local art and culture. However, tendency of act indicator from 7 respondents or 38,9% gave disagree responses because the students were in doubt if they got involved directly in preserving local art and culture. In the end, the results above proved that nationalism value from preserving local art and culture is hard to be founded, although the students have already known the function of art and culture. Therefore, parents and school have a role in supporting the action of preserving local art and culture in order to construct nationalism value for students.Tujuan penelitian ini adalah menjelaskan sikap siswa SMP Perintis 1 Bandar Lampung terhadap nilai nasionalisme dari pelestarian seni budaya lokal. Penelitian ini menggunakan metode deskriptif. Populasi penelitian ini adalah siswa SMP Perintis 1 Bandar Lampung yang berjumlah 184 siswa dengan sampel 18 siswa. Teknik pengumpulan data menggunakan angket, wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan rumus interval dan persentase. Hasil penelitian menunjukkan bahwa indikator pemahaman siswa dari 7 atau 38,9% responden termasuk kategori setuju yang menunjukkan bahwa siswa telah memahami pelestarian seni budaya lokal merupakan tanggung jawab generasi muda. Indikator penghargaan dari 8 atau 44,4% responden termasuk kategori setuju terhadap nilai nasionalisme dari pelestarian seni budaya lokal karena siswa memiliki peranan menjaga kestabilan nasional dengan melestarikan seni budaya lokal. Indikator kecenderungan bertindak dari 7 atau 38,9% responden termasuk kategori kurang setuju dikarenakan siswa masih ragu jika terlibat langsung dalam upaya pelestarian seni budaya lokal. Sehingga dari hasil penelitian tersebut dapat diketahui bahwa nilai nasionalisme dari pelestarian seni budaya lokal masih sulit ditemukan walaupun siswa sudah memahami fungsi dari seni budaya lokal tersebut, oleh karena itu orang tua dan sekolah memiliki peran dalam mendukung kegiatan pelestarian seni budaya lokal demi terciptanya nilai nasionalisme dalam diri siswa.Kata kunci: nilai nasionalisme, pelestarian, seni budaya